2014
DOI: 10.1186/2193-1801-3-412
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hospital malnutrition among cardiac patients: results from six nutrition screening tools

Abstract: Malnutrition is highly prevalent among hospitalized patients, ranging from 30% to 50% depending on the patient population and the criteria used for diagnosis. Identifying early those who are malnourished and at risk of malnutrition and intervening at an early stage will improve patients overall prognosis and will reduce the costs to the state. Even though cardiac patients are at risk of malnutrition, data on the prevalence of malnutrition among cardiology inpatients is limited. The aim of the study was to asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 37 publications
(53 reference statements)
0
18
0
Order By: Relevance
“…However, portion estimation using photographs seems to be the most practical method, as photographs can be made of any required portions of any food, and can be conveniently carried by interviewers [30]. Nevertheless, a previous study has confirmed that presenting aids in the form of photographs, other two-dimensional representations, or three-dimensional models appear to yield similar results [11].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, portion estimation using photographs seems to be the most practical method, as photographs can be made of any required portions of any food, and can be conveniently carried by interviewers [30]. Nevertheless, a previous study has confirmed that presenting aids in the form of photographs, other two-dimensional representations, or three-dimensional models appear to yield similar results [11].…”
Section: Discussionmentioning
confidence: 99%
“…A study has found that the errors which are frequently occurring when estimating portion sizes using photographs, were generally small (<10%) to moderate (10-25%) [11]. Nelson et al have revealed the flat slope phenomenon and a regression to mean effect; small portion sizes are overestimated, large portion sizes are underestimated and medium portion sizes usually estimated comparatively well [32].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Data were collected by a trained medical officer. Details of the study have been reported elsewhere (18). Only the patients, giving informed written consent, were included.…”
Section: Study Design and Subjectsmentioning
confidence: 99%